Development of Science Literacy-Based Cognitive E-Assessments on Chemical Bonds - Tania, Lisa; Saputra, Andrian; Hendriani, Fresti; Sahaya, Hilna Diana (Jurnal Pendidikan MIPA, 2022)
This study aims to develop scientific literacy-based cognitive e-assessments on chemical bonds and describe the validity, teacher responses, and student responses to the developed e-assessment. The research design used in this study was a research and development (R&D) design according to Gall, Borg, & Gall (1996). The instruments used in this study were expert validation questionnaires, teacher response questionnaires, and student response questionnaires. The data obtained from validators, teachers, and students were then analyzed by descriptive statistical analysis method. This scientific literacy-based cognitive e-assessment uses 4 aspects of scientific literacy, namely aspects about the knowledge needed for intelligent participation in science-based social problems, aspects about the ability to think critically about science and dealing with scientific expertise, aspects about understanding science and its applications, and aspects about understanding science and its applications. knowledge of the risks and benefits of science. This e-assessment was created to measure students' scientific literacy. The results of expert validation and teacher responses on aspects of content suitability, construction aspects, and readability aspects indicate a very feasible category. The results of student responses on the construction aspect and the readability aspect showed the criteria were very feasible. Thus, the scientific literacy-based cognitive E-assessment on the chemical bonding material developed can be said to be valid and feasible to use.Keywords: cognitive e-assessment, chemical bonding, scientific literacy.DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1320-1327